BUILDING FUNCTIONAL PROJECT ORGANIZATION: EVIDENCE FROM INDONESIA CEMENT PROJECTS - Effnandya, Aini Nur Febianti; Effnandya, Annisa Farahmei; Subiyanto, Effnu (Research In Management and Accounting (RIMA), 2025)
The aim of this study is to provide a practical established of functional project organization based on empirical experience from executing several cement projects in Indonesia. This study developed a mixed interdisciplinary case study, content analysis, and descriptive analysis. First, we employed a case study to collect data and information on the cement projects in Indonesia from 2008 to 2023. Second, we conducted content analyses to examine preliminary findings from the first stage. Finally, we developed a descriptive analysis to draw conclusions, recommendations, and suggestions. This study justified that the engineering, procurement, and construction contract (EPCC) organization was the best fit and received adequate support to be applied in the cement projects. This type of organization has been recognized by practitioners of cement projects in Indonesia. An important note is that the organization must have a framework chart authorization to govern finance circulation.